Adjustment of the Universal Soil Loss Equation in runof f plots located in a region of central Mexico - Valdivia-Martínez, Oscar; Peña-Uribe, Gabriel de Jesús; Rufino-Rodríguez, Fernando; Torres-González, Jorge Alejandro; Meraz-Jiménez, Antonio de Jesús; López-Santos, Armando (REVISTA TERRA LATINOAMERICANA, 2022)
Due to the lack of methods to accurately estimate soil loss in Mexico, experimental studies should be conducted to estimate erosion based on validated data. Therefore, the objective of this research is to estimate the Annual Erosion Rate (A) for various soil covers using the Universal Soil Loss Equation (EUPS) and adjusting its relationship with the Sediment Generation Index (IGS) obtained in experimental batches. The results show that during the period and conditions of this study, EUPS underestimates the value of A, when estimating the erosivity of the rain with the Modif ied Fournier Index (RIMF), in treatments with Natural Vegetation (VN) and Roturation with Esquilmo (RE). Soils without covers evidenced a higher IGS. Likewise, the equations obtained with the relationship IGS vs A, of the treatments with Bare (SD) and Broken Soil (RT) can be used to adjust the edaphic loss rate in soils with the same characteristics as those of the study, complying partially with the objective of this research.